Observation versus excision of lobular neoplasia on core needle biopsy of the breast - Schmidt, Hank; Arditi, Brittany; Wooster, Margaux; Weltz, Christina; Margolies, Laurie; Bleiweiss, Ira; Port, Elisa; Jaffer, Shabnam (Breast cancer research and treatment, 2018)
Purpose Controversy surrounds management of lobular neoplasia (LN), [atypical lobular hyperplasia (ALH) or lobular carcinoma in situ (LCIS)], diagnosed on core needle biopsy (CNB). Retrospective series of pure ALH and LCIS reported “upgrade” rate to DCIS or invasive cancer in 0–40%. Few reports document radiologic/pathologic correlation to exclude cases of discordance that are the likely source of most upgrades, and there is minimal data on outcomes with follow-up imaging and clinical surveillance. Methods Cases of LN alone on CNB (2001–2014) were reviewed. CNB yielding LN with other pathologic findings for which surgery was indicated were excluded. All patients had either surgical excision or clinical follow-up with breast imaging. All cases included were subject to radiologic–pathologic correlation after biopsy. Results 178 cases were identified out of 62213 (0.3%). 115 (65%) patients underwent surgery, and 54 (30%) patients had surveillance for > 12 months (mean = 55 months). Of the patients who underwent surgical excision, 13/115 (11%) were malignant. Eight of these 13 found malignancy at excision when CNB results were considered discordant (5 DCIS, and 3 invasive lobular carcinoma), with the remainder, 5/115 (4%), having a true pathologic upgrade: 3 DCIS, and 2 microinvasive lobular carcinoma. Among 54 patients not having excision, 12/54 (22%) underwent subsequent CNB with only 1 carcinoma found at the initial biopsy site. Conclusions Surgical excision of LN yields a low upgrade rate when careful consideration is given to radiologic/pathologic correlation to exclude cases of discordance. Observation with interval breast imaging is a reasonable alternative for most cases.